Laparoscopic one-stage orchiopexy for transverse testicular ectopia - Sung Ryul Lee (Elsevier, 2017)
In most patients with a non-palpable undescended testis, the location of each testis is near each inguinal canal, irrespective of whether the testis is in the abdominal cavity or in the inguinal canal. Preoperative diagnostic ultrasonography can be used to determine the status and location of the testis, and orchiopexy is recommended before 18 months of age. In recent years, laparoscopic operations have been frequently performed, and treatment has been simultaneously provided with diagnosis. Here I report successful laparoscopic one-stage testicular vessel-preserving orchiopexy in two cryptorchidism patients with both testes on one side of the inguinal canal. Laparoscopic orchiopexy is technically applicable and safe, without prolongation of the operation time or an increase in postoperative complications. Laparoscopic one-stage testicular vessel-preserving orchiopexy is an effective treatment approach for a non-palpable undescended testis located in the unilateral inguinal canal.